1992
DOI: 10.1002/jcp.1041520220
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related alterations in superoxide anion generation in mouse peritoneal macrophages studied by repeated stimulations and heat shock treatment

Abstract: The ability of thioglycollate-elicited peritoneal macrophages (PM) from young and senescent mice to generate superoxide anions (O2-) under repeated stimulation or thermal stress was studied using either zymosan, opsonized zymosan (OZ), or phorbol myristate acetate (PMA). A diminished capacity to recover from repeated stimulation was found with aging. When stimulated for a second time 24 hours after the primary stimulation, PM from young animals generated 80% of the initial O2- responses to either zymosan, or O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…A similar decline in extracellular and intracellular O 2 .-production was also observed in aged mice, relative to their young counterparts. These observations are concurrent with previous report (Lavie et al 1992). Contrary to peritoneal macrophages, the production of ROI by splenic macrophages increased in aged mice.…”
Section: Resultssupporting
confidence: 93%
“…A similar decline in extracellular and intracellular O 2 .-production was also observed in aged mice, relative to their young counterparts. These observations are concurrent with previous report (Lavie et al 1992). Contrary to peritoneal macrophages, the production of ROI by splenic macrophages increased in aged mice.…”
Section: Resultssupporting
confidence: 93%
“…Some authors have shown this capacity to be diminished or unchanged in aged subjects (De la Fuente, 1985;Ginaldi et al, 1999;Krause et al, 1999), while others have found an increased phagocytic capacity of macrophages during old age (De la Kay, 1996;Ortega et al, 1993Ortega et al, , 2000Wustrow et al, 1982). Similarly controversial are the results about the oxygen-dependent microbicide processes in old individuals (Alvarez et al, 1996;Alvarez and Santa Maria, 1996;De la Fuente, 1985Ding et al, 1994;Lavie et al, 1992;Ortega et al, 2000). Few studies have analyzed the antigen-presenting capacity of macrophages from aged individuals that seems to be reduced or unimpaired (De la Fuente, 1985;Perkins et al, 1982;Vetvicka et al, 1985).…”
Section: Aging and Macrophagesmentioning
confidence: 90%
“…Even though it has been demonstrated that macrophages from different species and different organs can respond differently to an array of stimuli (radiation, drugs, toxins, metal ions), few and controversial studies have addressed the influence of age on the function of macrophages. Studies performed in senescent individuals show an increase in mononuclear phagocyte system function, while others, report a decrease in immune system activity . It is noteworthy that today, metallic biomedical devices are not only employed to treat adult patients but are increasingly being used in the young.…”
Section: Introductionmentioning
confidence: 99%